Le soleil devient un mythe - Ildikó Lőrinszky (Flaubert: Revue Critique et Génétique)
Starting from an enigmatic phrase in Flaubert’s correspondence, dating from 1858, this article examines the relation between the Sun and myth, which constitutes one of the key elements of the mythological dimension of Salammbô. It especially focuses on the treatment of this question in two representative works of mythographic studies, The Origin of All Religious Worship by Charles-François Dupuis, and Les Religions de l’Antiquité..., the French adaptation of Frédéric Creuzer’s Symbolik und Mythologie der alten Völker by Joseph-Daniel Guigniault. The French version of Creuzer’s great synthesis, supplied with a remarkable set of prints, was abundantly consulted by Flaubert when writing his Carthaginian novel. In Salammbô, myth takes on various forms. Analyzing this text might lead one to reconsider “the right way” to use myths — a problem all writers (and readers) find themselves confronted with.